2008
DOI: 10.3354/meps07562
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of a single embryo/planula in the reef-building coral Acropora intermedia

Abstract: O 2 consumption of a single embryo/planula at each developmental stage was monitored in the reef-building coral Acropora intermedia using an optical O 2 -sensing system with our original micro-chamber system (6.28 µl). The lowest rate of O 2 consumption was observed in unfertilized eggs. After fertilization, O 2 consumption increased and remained constant until the prawn chip blastula stage. However, O 2 consumption began to increase again during the bowl-shaped blastula stage, which involves the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…This finding may, in part, contribute to the higher thermal tolerance of P. damicornis larvae compared to A. tenuis larvae. The lower larval respiration rates are consistent with the observation that coral larvae can maintain a low metabolic rate after becoming competent to metamorphose [13,19]. Putnam et al [20] suggested that larvae of P. damicornis are physiologically well suited to fluctuating temperatures.…”
Section: Discussionsupporting
confidence: 69%
“…This finding may, in part, contribute to the higher thermal tolerance of P. damicornis larvae compared to A. tenuis larvae. The lower larval respiration rates are consistent with the observation that coral larvae can maintain a low metabolic rate after becoming competent to metamorphose [13,19]. Putnam et al [20] suggested that larvae of P. damicornis are physiologically well suited to fluctuating temperatures.…”
Section: Discussionsupporting
confidence: 69%
“…Generally, long survival of larvae implies the availability of large initial energy reserves that the larva is either able to supplement during its life, e.g. via symbiotic zooxanthellae or potentially even through the uptake of dissolved organic matter (DOM), or that it is able to control its metabolic rates (Richmond 1987, Manahan 1990, Ben-David-Zaslow & Benayahu 2000, Harii et al 2007, Okubo et al 2008). The red gorgonian P. clavata is aposymbiotic and there is no evidence of DOM uptake by its larvae, although the latter cannot be excluded.…”
Section: Expt 2 Effects Of Thermal Stress On Larval Survival and Metmentioning
confidence: 99%
“…For this purpose, paramecia were confined in a small volume of the chamber (<1 ml) and the oxygen consumption rate and the swimming speed were measured simultaneously from the same specimens. Oxygen consumption was measured by means of an optic fluorescence oxygen sensor (Okubo et al, 2008). Because this sensor has proved not to alter the amount of dissolved oxygen unlike oxygen electrodes, which consume a substantial amount of oxygen during the measurement procedure, it is ideal for measuring the oxygen concentration in a small volume of a sample.…”
Section: Introductionmentioning
confidence: 99%